2022
DOI: 10.1038/s41541-022-00532-7
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated rabies-vectored SARS-CoV-2 vaccine provides long-term immune response unaffected by vector immunity

Abstract: The objective of this study is to further analyze recombinant rabies virus-vectored SARS-CoV-2 vaccine, CORAVAX, as an effective COVID-19 vaccine strategy. CORAVAX has proven immunogenic and protective against SARS-CoV-2 in animal models. Here, we have screened adjuvants for the highest quality antibody titers, negated the concern of pre-existing rabies-vector immunity, and established its potential as a long-term COVID-19 vaccine. We have tested toll-like receptor 4 (TLR4) agonists, inflammasome activators, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…RABV vaccination often protects long-term, and revaccination is rarely needed even after decades of previous immunization. We have shown that the RABV platform elicits long-term immunity to the foreign inserted antigen in a recombinant SARS-CoV-2 vaccine in mice 23 , and FILORAB1 has demonstrated durability of antibody responses in NHPs to 1 year 24 .…”
Section: Introductionmentioning
confidence: 99%
“…RABV vaccination often protects long-term, and revaccination is rarely needed even after decades of previous immunization. We have shown that the RABV platform elicits long-term immunity to the foreign inserted antigen in a recombinant SARS-CoV-2 vaccine in mice 23 , and FILORAB1 has demonstrated durability of antibody responses in NHPs to 1 year 24 .…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that splenic lymphocytes in animals after a long time from full vaccination can be rapidly recalled to an activated state when encountering the same antigens. Deeply, the results also reflected that draining LNs may play an important role in the early stage after mRNA vaccine immunization, while the long‐term rapid immune responses could be more dependent on the spleen 37,38 . Interestingly, the results also showed that a lower activation of B and T lymphocytes in mice vaccinated with the highest dose.…”
Section: Resultsmentioning
confidence: 77%
“…The inactivated RABV vaccine has been safely administered to millions of people, and our inactivated RABV-vectored vaccines have completed or are beginning clinical trials for COVID-19 and Lassa Fever, respectively. We have long-term immunogenicity data for the RABV vaccine platform at 1 year for SARS-CoV-2 in mice (in press), 20 and for Ebola, Sudan, Marburg, and Lassa fever virus in NHPs. 21 By network meta-analysis of all EBOV vaccines in humans, rVSV-ZEBOV exhibited the most risk-benefit, followed by the rAd5.ZEBOV-GP and ChAd3-EBO-Z vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…19 RABV vaccination often protects long-term, and revaccination is rarely needed even after decades of previous immunization. We have shown that the RABV platform elicits long-term immunity to the foreign inserted antigen in a recombinant SARS-CoV-2 vaccine in mice (in press), 20 and FILORAB1 has demonstrated durability of antibody responses in NHPs to 1 year. 21 The ability of adjuvants to affect vaccine immune responses is an important consideration in vaccine development, especially for inactivated vaccine platforms.…”
Section: Introductionmentioning
confidence: 99%